2015
DOI: 10.1016/j.protis.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Kleptochloroplast Enlargement, Karyoklepty and the Distribution of the Cryptomonad Nucleus in Nusuttodinium (= Gymnodinium) aeruginosum (Dinophyceae)

Abstract: The unarmoured freshwater dinoflagellate Nusuttodinium (= Gymnodinium) 22 aeruginosum retains a cryptomonad-derived kleptochloroplast and nucleus, the former 23 of which fills the bulk of its cell volume. The paucity of studies following 24 morphological changes to the kleptochloroplast with time make it unclear how the 25 kleptochloroplast enlarges and why the cell ultimately loses the cryptomonad nucleus. 26We observed, both at the light and electron microscope level, morphological changes to 27 the klept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…While sequestration of nuclei and chloroplasts along with other prey organelles is well known for a few dinoflagellates species (Dodge, 1971; Farmer and Roberts, 1990; Horiguchi and Pienaar, 1992; Okamoto and Inouye, 2005; Gast et al, 2007; Yamaguchi et al, 2011; Onuma and Horiguchi, 2013, 2015; Kim et al, 2014), enlargement of the sequestered prey nucleus has not been reported in any of studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While sequestration of nuclei and chloroplasts along with other prey organelles is well known for a few dinoflagellates species (Dodge, 1971; Farmer and Roberts, 1990; Horiguchi and Pienaar, 1992; Okamoto and Inouye, 2005; Gast et al, 2007; Yamaguchi et al, 2011; Onuma and Horiguchi, 2013, 2015; Kim et al, 2014), enlargement of the sequestered prey nucleus has not been reported in any of studies.…”
Section: Discussionmentioning
confidence: 96%
“…The sequestered prey nucleus has been inferred to allow the host cell to exploit photosynthetic performance of its sequestered prey chloroplasts; e.g., the dinoflagellates Amylax triacantha , Nusuttodinium aeruginosum , and N. myriopyrenoides and the ciliate M. rubrum (Johnson and Stoecker, 2005; Johnson et al, 2007; Kim et al, 2014, 2016; Onuma and Horiguchi, 2015). A few molecular and transcriptome studies focusing on the photosynthetic ability of M. rubrum in association with the sequestered prey nucleus (Johnson et al, 2007; Lasek-Nesselquist et al, 2015; Kim et al, 2016) have shown expression of nuclear-encoded plastid-targeted algal genes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they may have sequestered the engulfed plastids and nuclei from the central phagosome into special vesicles in which these organelles were protected from digestion, as found in the dinoflagellate Amylax triacantha (Kim et al., ). Further, these hosts may have modified the engulfed plastids, such as by their enlargement, as observed in the dinoflagellate Nusuttodinium (= Gymnodinium ) aeruginosum (Onuma & Horiguchi, ).…”
Section: New Hypotheses For the Acquisition Of Red Multimembrane Plasmentioning
confidence: 99%
“…Moreover, their host cells possess highly advanced mechanisms for ingestion and maintenance of these algal cells or their organelles (e.g. Johnson et al, 2007;Kim et al, 2012;Onuma & Horiguchi, 2015).…”
Section: Kleptoplastid Systems In Ciliates and Dinoflagellates: A mentioning
confidence: 99%
“…Certain species of heterotrophic dinoflagellates engulf eukaryotic algae and use them as temporary chloroplasts (called "kleptoplasts") for a period of days to weeks before digesting them. In certain cases, the kleptoplast divides in accord with dinoflagellate cell division and is inherited for a number of generations (6). A few dinoflagellate species maintain a eukaryotic algal unicell (i.e., containing a nucleus, mitochondria, Golgi apparatus, and so forth) as a permanent endosymbiont by synchronizing the endosymbiont cell division to the host cell cycle (7,8).…”
mentioning
confidence: 99%